2016
DOI: 10.1016/j.cub.2016.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Longitudinal Study Challenges the Existence of Neonatal Imitation in Humans

Abstract: Human children copy others' actions with high fidelity, supporting early cultural learning and assisting in the development and maintenance of behavioral traditions [1]. Imitation has long been assumed to occur from birth [2-4], with influential theories (e.g., [5-7]) placing an innate imitation module at the foundation of social cognition (potentially underpinned by a mirror neuron system [8, 9]). Yet, the very phenomenon of neonatal imitation has remained controversial. Empirical support is mixed and interpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
202
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(216 citation statements)
references
References 32 publications
6
202
0
3
Order By: Relevance
“…Among such expressions, the smile-the bilateral stretching of the lips by the zygomaticus major muscles-is remarkable for being produced and recognised early in development (Oostenbroek et al, 2016) and across cultures (Ekman et al, 1969). Smiling is not only perceived visually, but can also be heard in spoken voice (or smiled speech, Tartter, 1980;Basso and Oullier, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Among such expressions, the smile-the bilateral stretching of the lips by the zygomaticus major muscles-is remarkable for being produced and recognised early in development (Oostenbroek et al, 2016) and across cultures (Ekman et al, 1969). Smiling is not only perceived visually, but can also be heard in spoken voice (or smiled speech, Tartter, 1980;Basso and Oullier, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…If correct, this would suggest that the ability to imitate others is a special-purpose cognitive module which is genetically inherited (Meltzoff & Decety, 2003;Oberman, Hubbard, & McCleery, 2014). However, the studies of newborns have been challenged on a number of grounds, including by evidence that neonatal imitation may be limited to one action, tongue protrusion (Anisfeld, 1979;Ray & Heyes, 2011); by the suggestion that such 'imitation' may in fact be an arousal response (Jones, 1996(Jones, , 2006; and, most recently, by a large-scale longitudinal study which found no evidence for neonatal imitation and indicated that previous positive results were due to methodological and statistical artefacts (Oostenbroek et al, 2016).…”
mentioning
confidence: 99%
“…This may explain the variety of both positive and negative results on neonatal facial imitative responses (Ooestenbroeck et al ., 2016), in both humans and macaques, approximately 50% of individuals reliably imitate facial gestures – likely as a result of endogenous variation amongst infants in mirroring mechanisms. Analysis of the early developmental environments of different species may provide new avenues for research on the perception of mouth gestures and its neural and molecular basis, both in primate and prosimian neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Although the adaptive significance of neonatal imitation is not yet clear and is still debated (Oostenbroek et al ., 2016; Simpson et al ., 2014), understanding it as a experientially canalized or sensitive period phenomenon may pave the way to the identification of the different factors that play a role in its emergence and interindividual variability.…”
Section: Different Categories Of Mirror Neuronsmentioning
confidence: 99%